PENGARUH PENDIDIKAN BERBASIS MEDIA VIDEO ANIMASI TERHADAP PENGETAHUAN IBU TENTANG PROTEIN HEWAN UNTUK MENCEGAH BALITA STUNTING - Ningrum, Dedah; Setiadi, Diding Kelana; Sejati, Amanda Puspanditaning; Fauziyah , Roro Nur (JURNAL RISET KESEHATAN POLTEKKES DEPKES BANDUNG, Online ISSN 2579-8103, 2024)
Stunting cases in Girimukti village, North Sumedang sub-district, were 75 stunted toddlers (16.74%). Stunting in toddlers can be caused by the mother of toddlers having inadequate knowledge about feeding toddlers. One indirect factor that influences the incidence of stunting in children under five is the nutritional knowledge of mothers of toddlers.The study aimed to determine the effect of animated video media-based education on mothers' knowledge about food sources of animal protein to prevent stunting in toddlers. This study used a pre-experimental design and one group pre-test and post-test design. The research was conducted in July 2023, in Girimukti Village. The total sample was 46 mothers under five, consisting of 22 mothers with children under five with normal nutritional status and 24 mothers with children under five with stunting who lived in Girimukti Village. The sampling technique used purposive sampling technique. The research instrument used a knowledge questionnaire tested for validity and reliability and educational media in the form of animated videos and power points. The bivariate analysis used the Wilcoxon test. The result showed an increase in the average knowledge of mothers after being exposed to education using video-animated media; the average value of mother's knowledge during the pre-test was 70.24, and post-test was 79.04. The Wilcoxon signed rank test result is p-value<0.001 (p ≤ 0.05). The study concluded that there was an effect of video media-based education on increasing mother's knowledge about food sources of animal protein to prevent stunting in toddlers. Video-based media can be considered for use by health workers in nutrition education activities.